2010
DOI: 10.1002/polb.22064
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–volume–temperature data and surface tension of blends of poly(ethylene oxide) and poly(methyl acrylate) in the melt

Abstract: The pressure-volume-temperature behavior of miscible blends of poly(ethylene oxide) (PEO) and poly(methyl acrylate) (PMA) was studied over extended ranges of temperature and pressure. From pressure-volume-temperature data, the reduction parameters for the Flory-Orwoll-Vrij equation-ofstate were determined. It was found that reduction parameters as well as density, thermal expansion coefficient, and isothermal compressibility vary with composition in a nonlinear manner. The surface tension of the blends in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…It is often suggested that composites based on semicrystalline polymer matrices, notably polyolefins, exhibit a higher PTC intensity than composites based on amorphous polymers . The smaller change in resistivity in an amorphous polymer composite is related to the relatively small volume expansion, which is not sufficient to produce a significant and sudden change in resistivity . For example, composites with the same conductive filler type (Ni) and content showed a PTC intensity of six to seven orders of magnitude when based on semicrystalline polymers (i.e.…”
Section: Tuning Positive Pyroresistive Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often suggested that composites based on semicrystalline polymer matrices, notably polyolefins, exhibit a higher PTC intensity than composites based on amorphous polymers . The smaller change in resistivity in an amorphous polymer composite is related to the relatively small volume expansion, which is not sufficient to produce a significant and sudden change in resistivity . For example, composites with the same conductive filler type (Ni) and content showed a PTC intensity of six to seven orders of magnitude when based on semicrystalline polymers (i.e.…”
Section: Tuning Positive Pyroresistive Behaviourmentioning
confidence: 99%
“…21,37 The smaller change in resistivity in an amorphous polymer composite is related to the relatively small volume expansion, which is not sufficient to produce a significant and sudden change in resistivity. 38,39 For example, composites with the same conductive filler type (Ni) and content showed a PTC intensity of six to seven orders of magnitude when based on semicrystalline polymers (i.e. PE, PEO, polyethylene adipate) but only one to three orders of magnitude when based on amorphous polymers (i.e.…”
Section: Ptc Intensitymentioning
confidence: 99%
“…On the contrary, composites based on semi‐crystalline polymers, such as PE, PEO and polyethylene adipate (PEA) showed ∼6 to 7 orders of magnitude change in resistivity close to their melting points. The smaller change in resistivity with an amorphous polymer composite was attributed to the fact that the volume of amorphous polymer composites expand gradually with increasing temperature16 which is insufficient to produce significant changes in resistivity.…”
Section: Ptc Effects Of the Several Investigated Polymersmentioning
confidence: 99%
“…On the other hand, the large PTCs of semi‐crystalline polymers were attributed to the transformation of the crystalline phase to amorphous phase, which resulted in: (1) a large volume expansion near the melting point,16–18 and (2) increased the inter‐particle distance to a greated extend in between the conducting particles and its corresponding conductivity 19. These are the main reasons why the majority of existing resettable fuses and self‐limiting heating elements are based on semi‐crystalline polymers, in which the self‐limiting region is located near the melting point of the selected polymer 9.…”
Section: Ptc Effects Of the Several Investigated Polymersmentioning
confidence: 99%
“…Extensive studies on organic solvent-free electrolytes, for example on solid polymer electrolytes (SPEs), have been carried out [ 6 , 7 ] since 1980. One of the popular polymer hosts for SPEs is poly(ethylene oxide) (PEO), which is a semi-crystalline polymer with crystallinity amount up to 70% [ 8 , 9 , 10 , 11 , 12 ]. It is widely accepted that ionic percolation mainly takes place in the amorphous regions of polymer [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%